The Events in the Arab World, the Recent Global Crisis, and the World Bank Group - Indrawati, Mulyani (World Bank, Washington, DC, 2012)
This quick note is to provide the reader with a perspective on how the World Bank Group has been challenged by and has responded to recent global crises. However, at this historical moment, one cannot begin to write of global or regional issues without noting the momentous events that are now sweeping across the Arab World. Every country is different, but common themes are emerging. The youth's messages are loud and clear: they want voice, employment, social and economic inclusion as well as good economic governance and sound institutions. This quick note will be mostly about what the World Bank has done and proposes to do to help the global and regional economy cope with the stresses and the transition. This program was designed to be a rapid response to short term needs. In addition, there is a need for longer term measures to enhance food security for all countries. At the country level, these measures comprise both investments and policy reforms. The policy issues are complex and require careful deliberation and attention to detail.